Human Security dalam Politik Mitigasi Covid-19 di Kota Pangkalpinang - safira, Putri sabilla; Ibrahim, Ibrahin; Murtasidin, Bahjatul (Jurnal Polinter : Kajian Politik dan Hubungan Internasional, 2023)
Since Covid-19 pandemic expands, and made world in a great global political dynamics. Global political dynamics focussed on treatment and prevention of Covid-19. The changes of regulations that happen periodically in order to find the more suits, efficients and effectives in finding problem solves for Covid-19 pandemic that’s happened currently. Countries are delivered efforts to survive and addapt in the ambience of pandemic Covid-19 era and not that ease. Thus ambience are mainly talk about human security. Furthermore, Covid-19 pandemic being the causes of structural order changes such as society, economic, and politic. Which, the aim of politic mitigation is to ensure the security setability and its human prosperity.
Keywords: Keywords: Politic Mitigation, Covid-19, Human Security, Regulation.